The Effects Of Standardised Extract Of Eurycoma Longifolia Jack (TAF 273) On The Female Rat Reproductive System - Abdulghani, Mahfoudh al-Musli Mohammed (2011)
Eurycoma longifolia Jack has shown promising pharmacological effects on the male reproductive system. A fraction of methanol extract, TAF 273 has shown improvement of male rat fertility and an increment in sperm numbers significantly. The objectives of the present studies are to test the hypothesis that TAF 273 could improve ovulation and other reproductive functions such as pregnancy outcome and sexual behaviour in female rats. TAF 273 was administered to female rats in various physiological and pathological states and several parameters were assessed for its biological effects. The results showed that TAF 273 significantly (p<0.01) increased ovulation in normal fertile (7.4 1.4) and hypofertile rats (11.0 4.6) compared with the control (5.6 1.4 and 3.4 1.5, respectively). It caused significant (p<0.001) improvement in the sexual behaviour of hypofertile rats; in rats treated with TAF 273, the lordosis quotient percentage after treatment was 86.9% compared with 22.7% before treatment. TAF 273 showed also significant protection against the detrimental effects of estradiol valerate (2 mg/rat) on ovarian and uterine tissues in polycystic ovarian rats. Moreover, TAF 273 significantly improved (p<0.05) the regularity of the oestrous cycle (OC), as well as pregnancy indices in testosterone-induced polycystic ovaries in rats; the rats treated with testosterone+TAF 273 (62.5%) and testosterone-treated rats (37.5%) exhibit normal OC.